Alternative energy sources and their role in reducing climate change - Abdel-Reda, Assist .Lecturer. Sarah Qasim (The International and Political Journal, 2023)
Several climatic changes have taken place during the few recent years. These changes are due to the continuous increase in the consumption of conventional energy including oil, gas, and coal. The largest percentage of this increase is caused by the major industrial countries whose goal is to achieve remarkable economic benefits at the expense of other countries and our environment. Today, global warming is among the most threatening environmental problems. This phenomenon is linked with other problems which are not easy to resolve, such as desertification, floods, and fires. Accordingly, the international society must make great efforts, and efficient cooperation among all the world’s nations in order to reduce the consumption of conventional energy through finding clean sources of energy, such as solar, water, and wind energy. This is the only way to save our environment from pollution and many other climatic problems